Mini-Laparoscopic Repair of Apical Pelvic Organ Prolapse (POP) by Lateral Suspension with Mesh - Mereu, L (Facts Views Vis Obgyn, 2018)
BACKGROUND: The aim of the present study is to analyze the feasibility, safety and learning curve of Mini- Laparoscopic Lateral suspension (LLS) for the treatment of apical and anterior defects following pelvic organ prolapse. METHODS: This is a cohort study on a retrospective series of 35 consecutive patients who underwent Mini-LLS for symptomatic POP between January 2014 and July 2016. All 35 patients were operated at the Gynaecological Unit in S. Chiara Hospital by two senior surgeons (S. Tateo and L. Mereu) and by a team with optimal skills in laparoscopic surgery. Patients were divided in two groups according to two different chronological phases: phase 1 identified the initial 12 cases, phase 2 the last 23 cases. We collected pre-, peri- and post-operative information to analyze the surgical outcomes and learning curve after Mini-LLS procedures. RESULTS: The mean LLS-Overall Time (OT) was 107.6 min (range, 185- 63 min). None of the patients had intra-operative complications. No conversion to laparotomy was necessary. The mean post-operative hospital stay was 58 hours in total (SD +/-22). Only in 3 cases (8.6 %) post-operative grade I complications were observed. Recurrence of POP was observed in 3 cases (8.6 %) during a mean follow up of 18 months. The mean OT decreased with experience, in particular after the first 12 cases (phase 1: 113.54 minutes versus phase 2: 104.43 minutes). In consequence, the reduction of time per procedure was statistically significant considering the Cusum Time (CT) (P < .05). CONCLUSIONS: Mini-LLS with mesh is a safe and reproducible technique with good anatomical results, low complication rates and a short learning curve.